Batas Usia Ideal Pernikahan Perspektif Maqasid Shariah - Holilur Rohman (Journal of Islamic Studies and Humanities, 2016)
An ideal marriage is a marriage that able to achieve the goal of becoming a family wedding sakinah, mawaddah warahmah. Al-Qur'an and Sunnah did not explain in detail about the limitations of marriageable age. There are three perspectives on the age limit to get married in Indonesia, first, the perspective of Islamic law, the second law No. 1 in 1974 allow a woman to get married at the age of 16 and men at age 19, the third, BKKBN which advocated age at marriage ideal namely the minimum age for women 21 years and for men 25 years old.But in different perspective, the ideal age of marriage maqasid shari'ah perspective for women 20 years and for men 25 years, because at this age considered to have been able to realize the goal wedding (maqasid shari'ah) such as: creating a family sakinah mawaddah wa rahmah, keeping the lineage, maintaining the pattern of family relationships, maintaining diversity and deemed ready in terms of economic, medical, psychological, social, religious.* * *Pernikahan yang ideal adalah pernikahan yang mampu mencapai tujuan pernikahan menjadi keluarga yang sakinah, mawaddah dan rahmah. Al-Qur’an dan as-Sunnah menjelaskan secara rinci tentang batasan usia menikah. Ada tiga perspektif mengenai batas usia menikah di Indonesia, pertama, perspektif hukum Islam, kedua, undang-undang no 1 1974 mengijinkan seorang perempuan menikah pada usia 16 tahun dan laki-laki pada usia 19 tahun, ketiga, BKKBN yang menganjurkan usia kawin yang ideal yaitu usia minimal bagi perempuan 21 tahun dan bagi laki-laki 25 tahun.. Akan tetapi usia ideal perkawinan perspektif maqasid shari’ah adalah bagi perempuan 20 tahun dan dan bagi laki-laki 25 tahun, karena pada usia ini dianggap telah mampu merealisasikan tujuan-tujuan pensyariatan pernikahan (maqasid shari’ah) seperti: menciptakan keluarga yang sakinah mawaddah wa rahmah, menjaga garis keturunan, menjaga pola hubungan keluarga, menjaga keberagamaan dan dipandang siap dalam hal aspek ekonomi, medis, psikologis, sosial, agama.